The Effect of Aloe Vera on Perineal Wound Healing in Postpartum Mothers at PMB A Jatisampurna Bekasi in 2024 - Desy Qomarasari; Anita Wulandari (Oshada, 2025)
In 2020, of a total of 1,951 spontaneous vaginal births, 57% of mothers received perineal sutures, 28% due to episiotomy and 29% due to spontaneous tears. Aloe vera is a plant that has been used to treat various diseases since ancient times. Aloe vera also contains polysaccharides that stimulate wound healing and new skin growth.  To determine the effect of aloe vera on healing perineal wounds in postpartum mothers at PMB A Jatisampurna Bekasi in 2024. This research uses a two group pretest and posttest design. The sample in this study was postpartum mothers who experienced perineal wounds, totaling 30 people. Sampling used total sampling. The research instrument uses an observation sheet. Data analysis used univariate and bivariate analysis using sample t test. Of the 30 respondents, based on the results of univariate analysis, the majority of respondents were aged 20-35 years (90%), had a high school education (50%), and working mothers (60%). Bivariate analysis showed that there was an effect of aloe vera on perineal wound healing in postpartum women (p value 0.000). There is an effect of aloe vera on healing perineal wounds in postpartum mothers.